ANALISIS DESKRIPTIF MINAT LATIHAN BERBAHASA INGGRIS SISWA KELAS III SD DI SDS AMIR HAMZAH - Sirait, Dahlia (JURNAL ILMU PENDIDIKAN, 2024)
This study aimed to look at a descriptive analysis of interest in practicing English in Class III elementary school students at SDS Amir Hamzah. The research method used a qualitative descriptive approach, this approach was directed at background and individuals holistically. The Research was carried out using various learning methods such as the use of fun media. Qualitative research linked the concept of learning English to the cultural background and characteristics of students. The Practical implementation of this method included mastery of technology, pedagogy and knowledge of learning content. The data analysis technique used the technique proposed by Miles and Huberman, namely data reduction, data presentation and verification and drawing conclusions. Checking the validity of the data was used trustworthiness through interviews. The results of this research shown that the implementation of English language training had been carried out well and smoothly in class III elementary school in Amir Hamzah. This could be seen from the development of learning in understanding the concepts of text material based on class III material which was running smoothly. This was increasing because the learning that took place apart from conveying theory also included practical exercises with related material that directly involved students' culture. A thematic integrated approach to learning was an approach that was integrated with students' culture and was linked to English texts so that students can understand what the teacher was saying and learning looked meaningful.